What can an open-economy DSGE model tell us about Hong Kong's housing market? - Michael Funke; Michael Paetz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper develops an open-economy DSGE model with a housing-market sector and a borrowing constraint. Contrary to standard conventions, domestic households are allowed to invest in foreign housing and vice versa. Using Bayesian methods, the model is applied to data for Hong Kong. The results show that Hong Kong s housing market is quite open to foreign investment, and perhaps more significantly, that variations in the loan-to-value ratio and housing preference shocks largely explain business cycle volatility.
URN:NBN:fi:bof-201408072223
Keywords: 330